Dispersion of Coils after Parent-Artery Occlusion of Radiation-Induced Internal Carotid Artery Pseudoaneurysm - Kiyosue, Hiro; Okahara, Mika; Tanoue, Shuichi; Sagara, Yoshiko; Matsumoto, Shunro; Mori, Hiromu; Arita, Miori; Watanabe, Tetsuo; Suzuki, Masashi (American Journal of Neuroradiology, 2004)
Summary: We report a rare complication following parent-artery occlusion in a patient with radiation-induced carotid pseudoaneurysms. Both the right internal carotid artery pseudoaneurysm and the recurrent external carotid artery pseudoaneurysm were treated by parent-artery occlusion with coils. Although rebleeding was not observed after the second embolization, angiography and endoscopy at the 12-month follow-up showed dispersion and migration of coils into the pharynx and the external auditory canal due to progressive radiation necrosis.